2011
DOI: 10.1007/s00114-011-0846-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of barley chromosome addition on the susceptibility of wheat to feeding by a gall-inducing leafhopper

Abstract: The maize orange leafhopper Cicadulina bipunctata is distributed widely in tropical and subtropical regions of the Old World and feeds on various Poaceae. The leafhopper is recognized as an important pest of maize in several countries. Adults as well as nymphs of C. bipunctata induce growth stunting and galls characterized by the severe swelling of leaf veins on many cereal crops including wheat, rice, and maize, but do not on barley. To clarify the mechanism of growth stunting and gall induction by C. bipunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Compensation by healthy tillers, which are not attacked by C. bipunctata, may mitigate the decline in yield caused by this symptom. No upheaval of leaf veins was observed on barley, sorghum, orchard grass, rhodes grass, sudan grass and guinea grass, although growth stunting was observed to some extent after C. bipunctata feeding 5,13,19 .…”
Section: Host Plantsmentioning
confidence: 89%
See 1 more Smart Citation
“…Compensation by healthy tillers, which are not attacked by C. bipunctata, may mitigate the decline in yield caused by this symptom. No upheaval of leaf veins was observed on barley, sorghum, orchard grass, rhodes grass, sudan grass and guinea grass, although growth stunting was observed to some extent after C. bipunctata feeding 5,13,19 .…”
Section: Host Plantsmentioning
confidence: 89%
“…stunted growth and upheaval of leaf veins) seem attributable to different physiological mechanisms. Kumashiro et al 5 examined the relationship between the degrees of growth stunting and upheaval of leaf veins, using six barley chromosome disomic addition lines of wheat. The two symptoms differed significantly among lines, but no significant correlation between the degrees of growth stunting and upheaval was detected.…”
Section: Mechanism Of Mwes Inductionmentioning
confidence: 99%
“…Improvement of the tolerant variety is another effective way to reduce MWES occurrence. A comparative study using barley chromosome disomic addition lines of wheat suggested that the tolerance to MWES is a quantitative trait controlled by multiple genes (Kumashiro et al, 2011). Such a quantitative difference in the tolerance would exist in maize although any differences in the degree of tolerance to MWES among present tolerant varieties has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, this species is known to occur in the Bonin Islands (Matsumura 1914), the Ryukyu Islands (Hayashi 2002), and Kyushu (Matsumura et al 2006;Matsukura et al 2009a;Kumashiro et al 2012). The leafhopper feeds on various Poaceae including important crops, such as maize, rice and wheat (Maramorosch et al 1961;Catindig et al 1996;Kumashiro et al 2011). Cicadulina bipunctata is a serious pest of maize because feeding by the leafhopper induces gall symptoms characterized by stunted growth and swollen leaf veins, which is referred to as the maize wallaby ear symptom (Grylls 1975;Ohata 1993).…”
Section: Introductionmentioning
confidence: 99%